AUTOANTIBODIES TO DNA IN BLOOD SERUM OF PATIENTS WITH HEMORRHAGIC FEVER WITH RENAL SYNDROME - D. G. Ishmukhametova; B. K. Temesgen; O. V. Vlasova; F. A. Babushkina (Медицинская иммунология, 2014)
Abstract. The levels of autoantibodies (AAbs) to double- and single-stranded DNA were studied in blood serum of sixty-one patients with hemorrhagic fever complicated by renal syndrome (HFRS), and twenty-five healthy persons using ELISA technique. In 95% of HFRS patients, the AAb levels to native (double-stranded) DNA were close to their values in healthy group (resp., 0,02-0,26 vs 0,06-0,27 arbitrary units). The levels of AAbs to single-stranded level in serum of patients significantly exceeded the threshold values for healthy persons (resp., 0,37-0,80 vs 0,14-0,57 arbitrary units). The average levels of AAbs to single-stranded DNA in the patients were increased twice, in comparison with normal values. These results demonstrate that hantavirus infection followed by development of HFRS are accompanied by activation of autoimmune processes in the organism, being associated with increased synthesis of AAbs to denatured DNA. AAbs to denatured DNA autoantibodies may participate in inflammatory destruction of kidney glomerular capillaries in HFRS.